(untitled) (TAMADDUN NURI JURNALI, 2024)
The article is devoted to the role of educational motivation in students’ satisfaction with educational activities and its psychological aspects, mental states of students in recognition by others, character traits. the content of the concepts of satisfaction with educational activities is revealed based on the scientific approaches of scientists.